Turnover isotópico do 13C em aves poedeiras - Ishizuka, Adriele Nayara Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to assess the turnover of carbon-13 on blood and plasma of laying hens by replacing C4 by C3 diets and C3 by C4 diets during the pre-laying period and initial laying period using the technique of stable carbon isotopes. We used 144 laying hens ramdomly divided into two treatments of which were fed by 42 days in the pre-posture period with diets based on rice grits and soybean meal, containing dicalcium phosphate or bovine meat and bone meal. On the beginning of laying period the diets were changed and the poultry of the pre-laying period were divided into four treatments whose diets contained ground corn, soybean meal and dicalcium phosphate; or ground corn, soybean meal and bovine meat and bone meal. On days 1, 2, 3, 5, 7, 10, 14, 19, 25, 32, and 42 of each period the blood and plasma from six birds per treatment were randomly collected. The half-life of blood and plasma of ASFB and ASFCO from pre-laying period were greater (17;4 and 15;5 days, respectively) than the treatments from initial laying period: ASFB-MSFB; ASFB-MSFCO; ASFCO-MSFB e MSFCOMSFCO (half-life of 11;10;11 and 9 for blood, and 2;2;2 and 2 days for plasma. We concluded that the age of hens influenced the blood and plasma turnover whereas the diets did not influenced them ...

Este estudo avaliou o turnover do carbono-13 em sangue e plasma de poedeiras na fase de pré-postura e inicial da postura, pela substituição de dietas C4 por C3 e C3 por C4, utilizando a técnica de isótopos estáveis de carbono. Foram utilizadas 144 aves divididas ao acaso em 2 tratamentos na pré-postura que receberam por 42 dias dietas à base de quireta de arroz e farelo de soja, fosfato bicálcico ou farinha de carne e ossos bovinos. Na fase inicial da postura, as aves dos dois tratamentos da fase de pré postura, foram divididas em quatro tratamentos, consitituídos de dietas à base de milho moído e farelo de soja, fosfato bicálcico ou farinha de carne e ossos bovinos. Aos 1, 2, 3, 5, 7, 10, 14, 19, 25, 32 e 42 de cada fase foram coletados sangue e plasma de 6 aves por tratamento. Os valores de meia-vida do sangue e plasma dos tratamentos ASFB e ASFCO da pré-postura foram maiores (17;4 e 15;5 dias respectivamente) do que os tratamentos ASFB-MSFB; ASFB-MSFCO; ASFCO-MSFB e MSFCO-MSFCO da postura inicial (meias-vidas de 11;10;11 e 9 para o sangue e 2;2;2 e 2 dias para o plasma). Deste modo, pode-se concluir que houve diferença da idade, mas não houve diferença em relação a dieta no turnover do sangue e plasma das aves. Termos para indexação: aves, carbono-13, diluição ...
Keywords: Ave poedeira; Analise por diluição isotopica; Isótopos estáveis; Sangue - Analise e quimica; Carbono 13; Stable isotopes